Beyond Asian exceptionalism: refugee protection in non-signatory states - Barbour, B (Refugee Studies Centre, University of Oxford, 2021)
Few Asian States have acceded to the Refugee Convention yet they may have laws, policies, practices or systems that can be of use in responding to refugees’ protection needs.